DIFFUSE LARGE B CELL LYMPHOMA PRESENTING AS BILATERAL ADRENAL NODULES: A CASE REPORT ON PRIMARY ADRENAL LYMPHOMA - Lee, Ainee Krystelle; Uy , Stefanie Lim (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE The case is of a 64-year-old Filipino female presenting with a 4-month history of unintentional weight loss with anorexia. Whole abdominal computed tomography with contrast showed large ovoid adrenal mass (7.4x4.5x3.8 cm right; 6.4x5.4x3.5 cm left) exhibiting heterogeneous and delayed enhancement: precontrast + 40 HU right, +36 HU left; contrast +50 HU right, +42 HU left; delayed phase +68 HU right, +71 HU left with <50% washout period. Upon completion of the hormonal work-up, she underwent laparoscopic exploration of the left adrenal mass. Histopathology revealed high-grade non-Hodgkin B Cell Lymphoma favoring Diffuse large B Cell Lymphoma. The patient is currently enrolled in frontMIND: a phase 3, multicenter, randomized, double-blind, placebo-controlled trial that compares tafasitamab with lenalidomide and R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) versus R-CHOP in previously untreated, high-intermediate and high-risk patients with newly-diagnosed DLBCL.